AKTIFITAS PEMUPUKAN FOSFOR (P) PADA LAHAN SAWAH DENGAN KANDUNGAN P-SEDANG - Yulinar Zubaidah; Rafli Munir (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2007)
This experiment was conducted at famer’s field in Kasang, Padang Pariaman Regency from July to November 2000. The experiment was designed in a randomized block design (RBD) with the treatment was five levels of SP36 fertilizer ( 0, 50, 75, 100, and 125 Kg/ha) and P starter (20 kg SP36/ha) with three replications. The results showed that the plant height was not affected by application of P fertilizer. Increasing P application tended to increase yield of rice. Application of 125 Kg SP36/ha gave the highest grain yield 7,6 ton/ha.Keywords: Soil P-Status, Rice field, P-fertilizer